Biomechanics a case-based approach - Flanagan, Sean P. 1968- (Jones & Bartlett Learning, 2014)
Biomechanics: A Case-Based Approach focuses on the comprehension, retention, and application of the core concepts of biomechanics using problem-based learning strategies. The book features a broad range of case studies and examples to illustrate key content throughout the text. Relevant and realistic problems provide students with the opportunity to associate what they're learning in class to real-life applications in the field. This text offers a unique approach to understanding biomechanical concepts through the use of mathematical problems. The conversational writing style engages students' attention while not sacrificing the rigor of the content. Case studies and real-world examples illustrate key content areas while competency checks, located at the conclusion of each major section, correspond to the first three areas of Bloom's Taxonomy: remember, understand, and apply. The text employs the technique of guided discover to ensure that all students understand the concepts of biomechanics. To accommodate a variety of student learning styles, content is presented physically, graphically, and mathematically.